Phosphorus MRS of healthy human spleen. (15th June 2022) - Weis, Jan; Jafar, Maysam; Liss, Per
Abstract : Phosphorus ( 31 P‐) MRS in vivo enables detection and quantification of important phosphorus‐containing metabolites in biological tissues. 31 P‐MRS of the normal spleen is challenging due to the relatively small volume and the larger distance between the spleen and surface coil. However, reference spectra of the healthy spleen are invaluable in studies of splenic malignancies and benign causes of splenomegaly, as well as in the study of its physiology. The purpose of this work was to investigate the feasibility of localized 31 P‐MRS of healthy spleen in situ in a clinically acceptable measurement time using a clinical 3 T MR scanner. In this work, 31 P spectra of five healthy volunteers were measured using single‐voxel image‐selected in vivo spectroscopy (ISIS). The measurement sequence was augmented by broadband proton decoupling and nuclear Overhauser effect enhancement. It is demonstrated that localized 31 P‐MRS of the spleen in situ using single‐voxel ISIS is feasible on a clinical 3 T scanner in a clinically acceptable acquisition time. However, results have to be corrected for the transmitter excitation profile, and chemical shift displacement errors need to be taken into consideration during placement of the volume of interest. Results presented here could be used as a reference in future studies of splenomegaly caused by haematological malignancies. Abstract : Phosphorus MRS of healthy human spleen in situ using single‐voxel ISIS is feasible on a 3 T scanner in a clinically acceptable acquisition time. Results should be corrected for transmitter excitation profile, and chemical shift displacement errors need to be taken into consideration during placement of the voxel.